2011
DOI: 10.1108/00400911111147686
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial intentions in developing and developed countries

Abstract: Purpose -This study proposes to use the Theory of Planned Behaviour to predict entrepreneurial intentions among students in five developing and nine developed countries. The purpose is to investigate whether entrepreneurial intention and its antecedents differ between developing and developed countries, and to test the theory in the two groups of countries. Design/methodology/approach -A total of 2,225 students in 13 countries participated in this study by responding to a structured questionnaire in classrooms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
314
5
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(369 citation statements)
references
References 39 publications
(67 reference statements)
36
314
5
14
Order By: Relevance
“…On the other hand many experimental findings show that the students from underdeveloped countries have sharper and stronger entrepreneurial mind-set than those the students of developed countries. The results support the "Theory of Planned Behavior" in underdeveloped and developed countries [11]. Other research studies have examined and argued that the reason is the utility resulting from desiring self-employment over habitual career opportunities -as it is described by Kabui and Maalu that individuals will select selfemployment as a professional opportunity if the value derived from this collection goes beyond the value resulting from employment.…”
Section: Introductionsupporting
confidence: 70%
“…On the other hand many experimental findings show that the students from underdeveloped countries have sharper and stronger entrepreneurial mind-set than those the students of developed countries. The results support the "Theory of Planned Behavior" in underdeveloped and developed countries [11]. Other research studies have examined and argued that the reason is the utility resulting from desiring self-employment over habitual career opportunities -as it is described by Kabui and Maalu that individuals will select selfemployment as a professional opportunity if the value derived from this collection goes beyond the value resulting from employment.…”
Section: Introductionsupporting
confidence: 70%
“…It has also been held that entrepreneurial disposition and intentions vary depending on the country (Janssen et al, 2011). Iakovleva et al, (2011) concluded that respondents from developing countries have stronger entrepreneurial intentions compared to those from developed nations. This is supported by empirical results that indicated students from developing countries have strong desirability in envisioning for their careers as entrepreneurs (Davey et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study as others wants to investigate the effect of psychometric variables on intention (Iakovleva, Kolvereid, & Stephan, 2011). The suggested variables are family history of being entrepreneurs, country, and type of a university (state or private), gender, work experience and self employed as shown in Appendix-A.…”
Section: Psychometric Variablesmentioning
confidence: 99%